PADUPADI YES OR NO (Pencegahan Diare dengan Edukasi PHBS menggunakan Media Video YES or NO) - Salsa Putri Irayani; Elwan Nanda Eka Putri; Dewi Anissa Qisti; Hafifah Fitriana; Syavira Anastakim Zulian Pitaloka (Jurnal Pengabdian Masyarakat Saga Komunitas, 2023)
Background: According to the World Health Organization (WHO), diarrhea is the number one cause of death for children under 5 years of age. In general, it is estimated that more than 10 million children under the age of 5 years die worldwide each year, of which about 20% are caused by diarrheal infections. In Indonesia, diarrheal disease is a special event (KLB) that is often accompanied by death. In the city of Bogor, the incidence of diarrhea in toddlers at the Tanah Sareal Health Center, Bogor City, in 2019 141 toddlers experienced diarrhea. In 2020, 107 children under five had diarrhea. And in 2021 21 toddlers had diarrhea. In PBL 1 and PBL 2, it is known that the main cause of diarrhea in children under five in the Tanah Sareal Work Area is the poor implementation of PHBS properly. Objectives: The purpose of this community service is to provide education in the form of counseling related to the application of PHBS in daily life at Posyandu Kartini RW 01 in the working area of ​​the Tanah Sareal Health Center, Bogor City. Methods: The method used is health education related to the prevention of diarrhea by implementing PHBS in the Tanah Sareal Health Center Work Area, Bogor City. This activity was carried out at the Kartini Posyandu RW 01 Tanah Seral, Bogor City with the title PADUPADI YES or NO (Diarrhea Prevention with PHBS education Using Video Media Yes or No). The target of this activity is parents or caregivers of toddlers who live in the Posyandu Kartini area, RW 01 Tanah Sareal, Bogor City. The educational media used are video and a crossword puzzle. To measure the success of this activity, the Pre Test and Post Test are used. Results: The results obtained from the provision of health education are increasing the knowledge of parents or caregivers of toddlers on the correct application of PHBS in daily life, which is 80.9% or as many as 17 parents or caregivers of toddlers. Conclusion: The conclusion obtained from the results of this counseling is that there are still many parents or caregivers of toddlers who do not know and have not implemented PHBS properly and correctly, this is one of the biggest causes of diarrhea in toddlers in the working area of ​​the Tanah Sareal Public Health Center, Bogor City.